2023
DOI: 10.1161/hhf.0000000000000080
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension in Congenital Heart Disease: A Scientific Statement From the American Heart Association

Abstract: Patients with pulmonary hypertension associated with congenital heart disease make up an increasing proportion of the total pulmonary hypertension population who bring with them added complexity because of underlying anatomical and hemodynamic abnormalities. Currently, no consensus recommendations are available on how to best manage this group of patients for either the primary cardiologist or pulmonary hypertension subspecialist, including timing of referral. The purposes of this document are (1) to describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 132 publications
0
16
0
Order By: Relevance
“…Our results revealed that the occurrence of LV underfilling pattern was associated with a higher risk of adverse cardiac events in PAH patients, irrespective of RV changes. Moreover, although CHD-PAH patients tend to have better outcomes compared to IPAH and CTD-PAH patients in previous studies, 28,29 in PAH patients without LV underfilling pattern, they presented with similar outcome.…”
Section: Discussionmentioning
confidence: 67%
“…Our results revealed that the occurrence of LV underfilling pattern was associated with a higher risk of adverse cardiac events in PAH patients, irrespective of RV changes. Moreover, although CHD-PAH patients tend to have better outcomes compared to IPAH and CTD-PAH patients in previous studies, 28,29 in PAH patients without LV underfilling pattern, they presented with similar outcome.…”
Section: Discussionmentioning
confidence: 67%
“…Management of portopulmonary hypertension (PoPH) and PAH associated with congenital heart disease (PAH-CHD) requires a multidisciplinary management approach [46]. Larger clinical trials have either underrepresented or excluded patients with these conditions, leading to treatment strategies often based on the experience of clinical experts or findings from retrospective studies [47].…”
Section: Treating Portopulmonary Hypertension and Pulmonary Arterial ...mentioning
confidence: 99%
“…PDE-5 inhibitors like sildenafil and tadalafil are cheaper options and work by increasing intracellular cGMP levels [48]. These agents have been shown to improve hemodynamics and exercise capacity [47]. Agents exerting their action through the endothelin pathway include bosentan, macitentan, and ambrisentan; they have achieved favorable results in patients with PAH-CHD.…”
Section: Treating Portopulmonary Hypertension and Pulmonary Arterial ...mentioning
confidence: 99%
See 1 more Smart Citation
“…During fetal development, the pulmonary vasculature undergoes intricate changes in preparation for the transition from intrauterine to extrauterine life [1]. However, certain factors, such as prematurity, congenital heart defects, or prenatal insults, can disrupt this process, leading to pulmonary vascular disease (PVD) in newborns [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%